2019
DOI: 10.3389/fphar.2019.00157
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Bromination Abolishes the Psychomotor Features and Pro-social Responses of MDMA (“Ecstasy”) in Rats and Preserves Affinity for the Serotonin Transporter (SERT)

Abstract: The entactogen MDMA (3,4-methylenedioxy-methamphetamine, “Ecstasy”) exerts its psychotropic effects acting primarily as a substrate of the serotonin transporter (SERT) to induce a non-exocytotic release of serotonin. Nevertheless, the roles of specific positions of the aromatic ring of MDMA associated with the modulation of typical entactogenic effects, using analogs derived from the MDMA template, are still not fully understood. Among many possibilities, aromatic halogenation of the phenylalkylamine moiety ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 64 publications
(82 reference statements)
1
4
0
Order By: Relevance
“…The results showed that 2-Br-4,5-MDMA completely prevented the ability of MDMA to impair visuospatial learning while maintaining the capacity of the molecule to increase prefrontal cortex LTP. These results agree with our previous findings regarding the influence of aromatic bromination of the MDMA template, as 2-Br-4,5-MDMA lacks almost all MDMA effects in vivo, highlighting the relevance of this structural modification in the alteration of the pharmacological profile of MDMA [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results showed that 2-Br-4,5-MDMA completely prevented the ability of MDMA to impair visuospatial learning while maintaining the capacity of the molecule to increase prefrontal cortex LTP. These results agree with our previous findings regarding the influence of aromatic bromination of the MDMA template, as 2-Br-4,5-MDMA lacks almost all MDMA effects in vivo, highlighting the relevance of this structural modification in the alteration of the pharmacological profile of MDMA [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…As mentioned earlier, previous findings in rat behavioral models of spontaneous psychomotor activity showed that 2-Br-4,5-MDMA may disrupt the classical effects of MDMA on spontaneous locomotion, consistently restoring control values [ 14 ]. In contrast, the results of the present study indicate that both MDMA and 2-Br-4,5-MDMA equally increase LTP in the prefrontal cortex, implying that C(2) bromination does not affect their ability to induce neuroplastic effects in that cortical area.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The tricylic antidepressant imipramine inhibits adrenaline-mediated aggregation in human platelets in vitro and decreases platelet 5-HT 2A receptor number (G omez-Gil et al, 2004). MDMA, like the SSRI citalopram, but in relatively high concentrations, inhibits collagen induced platelet aggregation (S aez-Briones et al, 2019). All of this suggests that inhibitors of monoamine transporters tend to inhibit mediator-induced platelet aggregation, and indeed the use of SSRIs is associated with a slightly decreased risk for acute MI (Schlienger et al, 2004).…”
Section: Cocainementioning
confidence: 99%